1990
DOI: 10.2151/jmsj1965.68.1_79
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sounding of Vertical Profiles of Atmospheric Ozone and Nitrous Oxide with a Tunable Diode Laser Heterodyne Spectrometer

Abstract: Observations of atmospheric ozone and nitrous oxide were performed with a laser heterodyne spectrometer using a tunable diode laser as a local oscillator at Sendai (38*15'N, 140*51'E), Japan from November 1988 to June 1989. The absorption line spectra measured with ultra high resolution of 0.0013 or 0.0027 cm-1 (40 or 80 MHz) were inverted by a conventional inversion method to retrieve vertical distribution profiles. The observed altitude range is from 5 to 30 km for ozone and from 1 to 35 km for nitrous oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Taguchi et al [1990a] reported results of an ozone profile retrieval using heterodyne measurements in the region of the 9.6-gm 0 3 absorption band. The error analysis by Taguchi et al [1990b] showed that their method is sensitive to the vertical profile in the 10-to 30-km altitude range. Pougatchev and Rinsland [1995] showed that in the case of carbon monoxide (CO), the analyzed spectrum contains features that are sensitive to dif- ferent parts of the vertical profile, so that retrieval of column amounts in two layers, from the surface to •7 km and from 7 km to the top of the atmosphere, is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi et al [1990a] reported results of an ozone profile retrieval using heterodyne measurements in the region of the 9.6-gm 0 3 absorption band. The error analysis by Taguchi et al [1990b] showed that their method is sensitive to the vertical profile in the 10-to 30-km altitude range. Pougatchev and Rinsland [1995] showed that in the case of carbon monoxide (CO), the analyzed spectrum contains features that are sensitive to dif- ferent parts of the vertical profile, so that retrieval of column amounts in two layers, from the surface to •7 km and from 7 km to the top of the atmosphere, is possible.…”
Section: Introductionmentioning
confidence: 99%